Formation of palm kernel oil esters nanoemulsion systems containing ibuprofen for topical delivery - Salim, Norazlinaliza (2013)
The formation of palm kernel oil esters (PKOE) nanoemulsions containing ibuprofen as a model drug, suitable for topical delivery was studied in oil/non-ionic surfactant/water system. Initially, several ternary phase diagrams with different non-ionic surfactants and with/without ibuprofen were constructed. From these ternary phase diagrams, PKOE/Cremophor EL/water and PKOE/Tween 80/water systems, which exhibited large isotropic region were selected for nanoemulsion preparation. Nanoemulsions with 2% ibuprofen, 18% of oil phase (oil and surfactant) and 80% of water were prepared by using low energy emulsification method. Six formulations were studied; CEL1, CEL2 and CEL3 from the PKOE/Cremophor EL/water system and T801, T802 and T803 from the PKOE/Tween 80/water system with different oil:surfactant ratios (10:90, 20:80 and 30:70, respectively).All formulations were characterized. The smallest droplet size was obtained at oil:surfactant ratio of 20:80 for CEL2 and T802 (20.48 nm and 16.52 nm, respectively). The largest droplet size was obtained at oil:surfactant ratio of 10:90 for CEL1 and T801 (32.87 nm and 84.51 nm, respectively). The polydispersity index indicated that formulations CEL2 and T802 had a narrow size distribution (<0.2) when compared to other samples (CEL1, CEL3, T801 and T803). The zeta potentials were between -1 and -19 mV, pH ranged from 3.53 to 3.93, the refractive index values were 1.347 to 1.361 and their viscosity values were between 3.00 and 5.00 cP for all the formulations. In the rheological study, the flow characteristics of the nanoemulsions with and without ibuprofen were investigated. Shear thinning increased in the nanoemulsions after the addition of 2% of ibuprofen, which exhibited apparent plastic behaviour. The viscosity decreased with increase in shear rate and reached a constant value at high shear rates for all the formulations containing ibuprofen. No significant differences were observed in the flow characteristics when the ratio of oil:surfactant increased. The spherical shape of the nanoemulsions was confirmed by Transmission Electron Microscopy (TEM) analysis. The mean droplet size ranged between 16 to 20 nm and revealed a good size distribution. For the 6-month stability studies, samples CEL2, CEL3, T802 and T803 were found to be stable with respect to homogeneity after centrifugation and storage at temperatures 4°C and 25°C, but unstable at 45°C.Due to the high kinetic stability of CEL2 and T802, their modification using different hydrocolloids (gellan gum, carrageenan and xanthan gum) namely T802G, CEL2G, T802C, CEL2C, T802X and CEL2X were investigated. No significant changes were observed in droplet size (~16-20 nm) but there was a significant difference in polydispersity indexes, zeta potentials, pH and their rheology after modification. For the 6-month study period, samples T802G, CEL2G, T802X and CEL2X were found to be stable, with no phase separation observed after centrifugation and storage at temperature 4°C and 25°C and unstable at 45°C. However T802C and CEL2C only stable when it stored at 4°C. The permeation of ibuprofen from PKOE nanoemulsions through a cellulose acetate membrane was studied using Franz diffusion cells. It was found that the permeation of ibuprofen from CEL2 (303.05 μg.cm-2.h-1, with the permeability coefficient (Kp) value of 0.170 cm/h) (p<0.05) was 1.78 times higher than T802 (254.94 μg.cm-2.h-1, Kp 0.140 cm/h). The addition of different hydrocolloids into CEL2 showed that carrageenan gave highest permeation of ibuprofen (79.2% release) at 8 h. However, when different penetration enhancers (terpenes) were added to CEL2, the permeation of ibuprofen through cellulose acetate membrane was hindered, decreasing to 22.3%. No significant differences (p>0.05) was observed when menthol, camphor and limonene were used as penetration enhancer.The ability of the nanoemulsions before (T802 and CEL2) and after modification (T802G and CEL2G) to deliver ibuprofen through Wistar rat skin were evaluated in-vitro using Franz diffusion cells. The in-vitro permeation data showed that the sample T802G (49.32 ± 4.88 μg .cm-2h-1, Kp 55.4 × 10-3 cm/h) increased the permeability of ibuprofen (p<0.05) 4.40 times over the sample T802 (25.25 ± 5.87 μg.cm-2h-1, Kp 12.6 × 10−3 cm/h). The percentage of ibuprofen released versus time from T802G was slightly greater than T802 up until 24h of the study. While, CEL2G (49.32 ± 4.88 μg.cm−2h−1, Kp 18.2 × 10−3 cm/h) decreased the permeability of ibuprofen when compared to the initial nanoemulsion, CEL2 (56.90 ± 17.90 μg.cm−2h−1, Kp 31.6× 10−3 cm/h). No significant differences were observed in percentage of release but there was a significant difference in permeability of ibuprofen up to 8h of the study.